Unlocking the Potential of Lacticaseibacillus rhamnosus 73 as a Ripening Agent in Semi-Hard Cheese After Freeze-Drying and a Six-Month Storage Period - Batistela, Mara Elisa (2025)
Dehydration and storage conditions used to preserve dairy cultures in the industry may negatively impact their viability and functionality. This study investigated the effects of freeze-drying and storage on the metabolic activity of Lacticaseibacillus rhamnosus 73 (L73). The strain’s viability after freeze-drying and storage, its metabolic activity in cultured milk, and its performance as a ripening agent in miniature cheeses were evaluated. Neither the freeze-drying process nor the storage conditions negatively affected its viability, as L73 maintained its initially high levels (>10 log cfu mL−1) throughout the storage period. L73 improved the overall quality of the cheeses, as a reduction in hydrophobic peptides (i.e., potential bitter peptides) was evidenced in cheese manufactured with L73. Furthermore, L73 exhibited protective properties, as evidenced by the decreased availability of compounds that could be used as energy sources by adventitious microorganisms (e.g., galactose, hippuric acid) and the increased production of lactic acid in both cultured milk and cheese.